Study protocol for a national observational cohort investigating frailty, delirium and multimorbidity in older surgical patients: the third Sprint National Anaesthesia Project (SNAP 3) - Peter Martin; Akshay Shah; Jose Lourtie; Judith Partridge; Karen Williams; Tom Poulton; Iain Keith Moppett; Carol Green; Bob Evans; Claire Swarbrick; Laura Cortes; Christine Taylor (BMJ Open)
Introduction Older surgical patients are more likely to be living with frailty and multimorbidity and experience postoperative complications. The management of these conditions in the perioperative pathway is evolving. In order to support objective decision-making for patients, services and national guidance, accurate, contemporary data are needed to describe the impact and associations between frailty, multimorbidity and healthcare processes with patient and service-level outcomes.Methods and analysis The study is comprised of an observational cohort study of approximately 7500 patients; an organisational survey of perioperative services and a clinician survey of the unplanned, medical workload generated from older surgical patients. The cohort will consist of patients who are 60 years and older, undergoing a surgical procedure during a 5-day recruitment period in participating UK hospitals. Participants will be assessed for baseline frailty and multimorbidity; postoperative morbidity including delirium; and quality of life. Data linkage will provide additional details about individuals, their admission and mortality.The study’s primary outcome is length of stay, other outcome measures include incidence of postoperative morbidity and delirium; readmission, mortality and quality of life. The cohort’s incidence of frailty, multimorbidity and delirium will be estimated using 95% CIs. Their relationships with outcome measures will be examined using unadjusted and adjusted multilevel regression analyses. Choice of covariates in the adjusted models will be prespecified, based on directed acyclic graphs.A parallel study is planned to take place in Australia in 2022.Ethics and dissemination The study has received approval from the Scotland A Research Ethics Committee and Wales Research Ethics Committee 7.This work hopes to influence the development of services and guidelines. We will publish our findings in peer-reviewed journals and provide summary documents to our participants, sites, healthcare policy-makers and the public.Trial registration number ISRCTN67043129.